The personality profi les of early adopters of energy-efficient technology - Ante Busic-Sontic; Franz Fuerst (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This study investigates whether energy efficiency investments are driven by differences in personality traits among homeowners. Using data on nearly 3,000 households in Germany, we estimate that compared to the median level, homeowners in the lowest quartile of Openness to Experience have 5.0%-23.4% lower propensity to invest in capital-intensive energy efficiency measures, while homeowners in the highest quartile of Agreeableness are 7.7%-18.0% less likelyto do so. Splitting the energy efficiency investments into two groups yields stronger effects of the same two personality traits for window modernisations and thermal insulation installations, whereas no impact of the personality traits is observed for solar energy and other alternative energy systems, possibly because subsidies for the latter were introduced much earlier in Germany, overriding any effects of personality traits in the investment decisions. These findings may also suggest that personality traits are of greater significance for marginal investors.
Keywords: 330; energy efficiency; personality traits; technology; diffusion; residential sector